Nano materials and innovative laser-based accelerators for cultural heritage - Veltri, Simona; Pantano, Pietro; Bonanno, Assunta; Antici, Patrizio (My University, 2017)
Università della Calabria, Dipartimento di Fisica
Keywords: Nanostructured materials